Comprehensive enhancement of mechanical strength, thermal conductivity, and oxidation resistance of W/Cu diffusion bonding joint via heterogeneous interface configuration theoretical design - Zida Wang; Jinghao Xu; Qi Wu; Shuwen Shang; Wei Shao; Jihua Huang; Shuhai Chen; Zheng Ye; Wanli Wang; Jian Yang (Journal of Materials Research and Technology, 2025)
To improve the Plasma-facing components (PFC) composed by plasma-facing materials (W) and heat-sink materials (Cu) in thermonuclear reactors, the mechanical strength, thermal conductivity, and oxidation resistance of W/Cu diffusion bonding joint were improved by heterogeneous interface configuration design. The results indicate that, as the W (110)/Cu (100) interface has the largest interface charge density, the Wad is the largest, which is 3.87 J/m2, and the maximum ideal tensile strain and tensile strength are 13 % and 7.84 GPa, respectively. Owing to its highest degree of electron delocalization, the W (110)/Cu (111) interface exhibits the largest thermal conductivity, which is 1.85 times that of the W (111)/Cu (111) interface and 2.84 times that of the W (110)/Cu (100) interface. Moreover, as the diffusion energy barrier at the W (110)/Cu (100) interface (3.62 eV) is much larger than W (110)/Cu (111) and W (111)/Cu (111) interface, which can be attributed to the O atom at the highest point of energy has the strongest bonding to the W/Cu atoms, W (110)/Cu (100) interface exhibits the most excellent oxidation resistance. Hence, it can be concluded that the W/Cu joint with a large number of W (110)/Cu (100) interfaces will exhibit the best mechanical strength, and oxidation resistance, and W (110)/Cu (111) interfaces has the most excellent thermal conductivity. This study not only contributes to enhancing the service performance of W/Cu composite structures, but provides valuable insights into the fundamental correlation between microstructural characteristics and the mechanical and thermal transport properties at heterogeneous interfaces.